Adjuvanticity of a CTLA-4 3′ UTR complementary oligonucleotide for emulsion formulated recombinant subunit and inactivated vaccines. Issue 18 (25th April 2017) - Li, Xin; Yang, Lei; Zhao, Peiyan; Yao, Yun; Lu, Fangjie; Tu, Liqun; Liu, Jiwei; Li, Zhiqin; Yu, Yongli; Wang, Liying
Highlights: CMD-1 could inhibit CTLA-4 expression on CD4 + T cells. CMD-1 could interfere CTLA-4 mRNA expression. CMD-1 could maintain CD80 and CD86 molecules on CD11c + cell. CMD-1 could improve recalled proliferation of CD4 + T cells and CD19 + B cells. CMD-1 could enhance antibody response to Cp or inactivated FMDV vaccines in mice. Abstract: Cytotoxic T-lymphocyte antigen 4 (CTLA-4) is recognized as a critical inhibitory regulator of T-cell proliferation and activation, opposing the action of CD28-mediated co-stimulation. Interfering or blocking CTLA-4 can result in continuous T-cell activation required for the full immune response to pathogenic microbes and vaccines. To test if nucleic acid-based CTLA-4 inhibitors could be developed into a novel adjuvant, we designed two oligonucleotides, CMD-1 and CMD-2, with the sequences complementary to the conserve regions identical between human and mouse CTLA-4 mRNA 3′ untranslated region (3′ UTR), and tested their in vitro effects on CTLA-4 production and their adjuvanticity for vaccines in mice. We found that CMD-1 inhibited the antigen-induced CTLA-4 up-regulation on the CD4 + T cells by interfering its mRNA expression, maintained higher levels of CD80 and CD86 on the CD11c + cells and promoted the recalled proliferation of the CD4 + T cells and CD19 + B cells, and that the CMD-1 enhanced the antibody response against recombinant PCV2b capsid protein or inactivated foot-and-mouth disease virus in both ICR and BALB/c mice. These data suggest that the CMD-1 could be used as a novel vaccine adjuvant capable of inhibiting inhibitory signals rather than inducing stimulatory signals of immune cells.